Collective action, empowerment, and conflict mediation - CGIAR Program on Collective Action and Property Rights (International Food Policy Research Institute, 2010)
The notion of ‘empowerment' has been more often deductively claimed than carefully defined or inductively assessed. In Indonesia, the Kecamatan Development Program (KDP) provides a good example on how program empowers participants (especially members of marginalized groups) by building their capacity to manage local conflict.